Managing Sustainable Development Projects Through a Risk-Oriented Framework - Кібік, Ольга Миколаївна; Кібік, О. М.; Kibik, Olha M.; Слободянюк, Ольга Василівна; Слободянюк, О. В.; Slobodianiuk, Olha V.; Котлубай, Вячеслав Олексійович; Котлубай, В. О.; Kotlubai, Viacheslav O.; Белоус, Катерина Вікторівна; Белоус, К. В.; Belous, Kateryna V.; et al. (Vancouver : Canadian Institute for Knowledge Development, 2025)
A number of global challenges, including the depletion of natural resources, environmental degradation, and growing inequality in access to resources, drive the relevance of achieving sustainable development goals and implementing relevant projects in key areas of modern society. The article describes the key aspects of a risk-based approach to managing sustainable development projects. The study used several general scientific methods of cognition, in particular, by synthesising literature, analysing statistical data, and comparing the legal frameworks of different countries; all aspects of risks for modern sustainable development projects were outlined, while systematisation and generalisation methods were used to form a system of the main stages and processes of risk ik-oriented management of sustainable development projects. Based on the results of the analysis of the main risks in implementing sustainable development initiatives, a structured management process that includes risk identification, assessment, prioritisation, and monitoring is required to ensure the efficiency and continuity of work on such projects. The risk-based approach minimises the negative impacts on a project's environmental, social and economic components aimed at sustainable development, ensuring the long-term effectiveness and sustainability of sustainable development projects. However, the effective implementation of this approach requires regular monitoring and review of the degree of risk exposure to consider the dynamics of changes in the business environment.
Kibik O. Managing Sustainable Development Projects Through a Risk-Oriented Framework / O. Kibik, O. Slobodianiuk, V. Kotlubai et al. // International Journal of Organizational Leadership. – Vancouver : Canadian Institute for Knowledge Development, 2025. - Vol. 14. - Р. 95-106. URL: https://doi.org/10.33844/ijol.2025.60462
Keywords: Risk-based management; Sustainable development Goals; Environmental standards; Economic growth; ESG